Agricultural Sector Investment on Gross Domestic Regional Product (GDRP) in West Java 2007-2012 - Ratni Heliati; Yovino Dwiputra (TRIKONOMIKA, 2016)
This study aims to determined the impact of investments in the agricultural sector to the Gross Domestic Regional Products (GDRP) of agriculture in West Java. The sample was taken from 26 regions in West Java.The results showed that Foreign Capital Investment (FCI) and Exchange rate have positive and significant impact to GDRP. Domestic Capital Investment (DCI) has positive effect of labor but not significantly to GDRP. BI Rate has significant negative effect on GDRP. Fixed effect model allows the analysis of individual securities to be interpreted as the position of the relative potency of a districts / cities. There are nine districts/cities that have a significant positive intercept. These districts are categorized as areas which contribute highly to agricultural sector. The highest sector is in Indramayu district, the second is in Sukabumi, Banjar, Subang and so on. Cimahi has the lowest score of intercept. Negative intercept is an area of low agricultural contribution, generally those which are categorized as industrial areas, such as Bandung, Cirebon, Bogor, Bekasi, Karawang. These areas are classified as industrial area which have negative contribution of agricultural sector to the GDRP.